Greenhouse gas emissions of a large, academic outpatient orthopedic center in the United States - Jett, Anna M.; Kothandaraman, Venkat; Bobbin, Esther; Sheldon, Seth; Colosi, Lisa M.; Meyer, Matthew J. (Frontiers in Health Services, 2025)
IntroductionHospitals and health systems create pollution as a byproduct of their work improving people's personal health. Pollution can harm human health. As part of a broad effort to comprehensively quantify a health system's pollution, we started with one group of pollutants, greenhouse gases, at a freestanding outpatient orthopedic center (OC).MethodsOC has clinic rooms, imaging, administrative offices, and a small ambulatory surgery center. It was newly constructed and received LEED Silver certification in 2022. The Greenhouse Gas Protocol was used to categorize emissions into Scope 1 (direct), Scope 2 (indirect from purchased energy), and Scope 3 (supply and value chain) emissions for fiscal year 2023.ResultsOC's total annual emissions were 11,049 metric tons of carbon dioxide equivalent (MTCO2e), with 2% from Scope 1, 17% from Scope 2, and 81% from Scope 3. Most Scope 3 emissions came from just three categories: patient transportation (52% of Scope 3 emissions), purchased goods and services (20%), and employee commuting (12%).DiscussionThis initial study highlights the significant contribution of Scope 3 emissions to an outpatient center's greenhouse gas footprint. It specifically identifies patient travel as a major contributor to emissions; this is particularly important since patient travel is not always included in Greenhouse Gas Protocol healthcare assessments and patient travel can be mitigated in some circumstances by utilizing telemedicine. The emissions distribution across scopes is similar to other international hospitals, indicating generalizability, though the high proportion of patient travel emissions is unique to this outpatient-focused facility.